Functional assessment of coronary artery stenosis by Doppler derived absolute and relative coronary blood flow velocity reserve in comparison with 99mTc MIBI SPECT. Issue 4 (1st October 1999) - Verberne, H J; Piek, J J; van Liebergen, R A M; Koch, K T; Schroeder-Tanka, J M; van Royen, E A
Abstract : OBJECTIVE: To determine the relation between the relative and absolute coronary blood flow velocity reserve (CFVR) compared with the results of 99m Tc MIBI single photon emission computed tomography (SPECT). METHODS: In 37 patients with one vessel disease, 99m Tc MIBI SPECT was performed before angioplasty, two to three weeks after angioplasty, and at six months' follow up. CFVR was measured distal to the stenosis (dCFVR) as well as in a reference coronary artery before angioplasty, immediately after angioplasty, and at late follow up. Relative CFVR (rCFVR) was calculated as the ratio between dCFVR and CFVR measured in the reference coronary artery. The optimal thresholds for reversible perfusion defects were calculated using receiver operating characteristic curves. RESULTS: The agreement for the full range of coronary artery stenosis (n = 107, mean (SD) diameter stenosis 48 (28)%, range 0–98%) between dCFVR (cut off value 1.9) and rCFVR (cut off value 0.65) with 99m Tc MIBI SPECT was 81% and 85%, respectively. In intermediate lesions (n = 49, diameter stenosis range 30–75%) the agreement between dCFVR (cut off value 2.0) and 99m Tc MIBI SPECT was 72%, which increased to 78% using the rCFVR (cut off value 0.65).There was a strong linear relation between dCFVR and rCFVR ( r  = 0.93, p < 0.0001). CONCLUSIONS: A best cut off value for dCFVR of 1.9 corresponds with a best cut off value of 0.65 for rCFVR, within the full range of coronary narrowings. Intracoronary blood flow velocity analysis could obviate the need for additional myocardial perfusion scintigraphy in the majority of patients.